The Innovative Role of Female Scholars in Shaping Islamic Education and State Policy - Mala, Asnal (Proceedings of International Conference on Muslim Society and Thought, 2024)
This study aims to explore the innovative role of female scholars in building Islamic education and state policy. The research employs a qualitative method, including a case study at the Hasyim Asy’ari Bangsri Islamic boarding school in Jepara and in-depth interviews with female scholar Bunyai Hindun Anisa, to uncover their significant contributions. The findings show that female scholars introduce new perspectives and initiatives that create more inclusive and progressive educational environments. Key findings include significant advancements in educational paradigms and the development of gender-responsive policy frameworks that meet community needs. The study also identifies challenges faced by female scholars, such as social and institutional barriers, and provides recommendations to support and strengthen their positive impact. By highlighting the importance of female education and leadership, the research emphasizes the need for greater recognition and support from various stakeholders. It demonstrates how female scholars play a crucial role in creating a more equitable, dynamic, and sustainable educational system.